The de Sitter Swampland Conjectures in the Context of Chaplygin-Inspired Inflation - Orfeu Bertolami; Robertus Potting; Paulo M. Sá (Universe, 2024)
In this work, we discuss the de Sitter swampland conjectures in the context of the generalized Chaplygin-inspired inflationary model. We demonstrate that these conjectures can be satisfied, but only in the region of the parameter space far away from the General Relativity limit. The cosmic microwave background data had already been found to restrict the allowed inflationary potentials of this model. Our results impose a further limitation on the possible potentials.